Correction of cilia structure and function alleviates multi-organ pathology in Bardet–Biedl syndrome mice. (3rd July 2020) - Husson, Hervé; Bukanov, Nikolay O; Moreno, Sarah; Smith, Mandy M; Richards, Brenda; Zhu, Cheng; Picariello, Tyler; Park, Hyejung; Wang, Bing; Natoli, Thomas A; Smith, Laurie A; Zanotti, Stefano; et al.
Abstract: Bardet–Biedl syndrome (BBS) is a pleiotropic autosomal recessive ciliopathy affecting multiple organs. The development of potential disease-modifying therapy for BBS will require concurrent targeting of multi-systemic manifestations. Here, we show for the first time that monosialodihexosylganglioside accumulates in Bbs2 −/− cilia, indicating impairment of glycosphingolipid (GSL) metabolism in BBS. Consequently, we tested whether BBS pathology in Bbs2 −/− mice can be reversed by targeting the underlying ciliary defect via reduction of GSL metabolism. Inhibition of GSL synthesis with the glucosylceramide synthase inhibitor Genz-667161 decreases the obesity, liver disease, retinal degeneration and olfaction defect in Bbs2 −/− mice. These effects are secondary to preservation of ciliary structure and signaling, and stimulation of cellular differentiation. In conclusion, reduction of GSL metabolism resolves the multi-organ pathology of Bbs2 −/− mice by directly preserving ciliary structure and function towards a normal phenotype. Since this approach does not rely on the correction of the underlying genetic mutation, it might translate successfully as a treatment for other ciliopathies.